Kajian Etnomatematika Dan Jati Diri Bangsa - Bambang Eko Susilo; Sri Adi Widodo (IndoMath: Indonesia Mathematics Education, 2018)
The significant development of ethnomatematics is expected to give a role to the nation's progress. The purpose of this research is to describe the role of ethnomatematics as one of the strength of national identity. The method used in this research is literature study by going through several stages: problem formulation, literature search, data evaluation, analysis, and interpretation. The results show that etnomatematics can present a lot of intellectual property which is largely a nation culture preserved centuries, so as to strengthen identity as a nation that has a great civilization.